Biomechanical understanding of blow-out fractures: A finite element study - KHALIL, Abdul-Karim; KHAFIF, Khodor; ATIEH, Amjad (International Arab Journal of Dentistry (IAJD), 2019)
Blow-out fractures are one of the most common fractures in maxillofacial trauma. Two mechanisms are thought to cause these fractures, the buckling mechanism and hydraulic mechanism. This study aims to compare between the two mechanisms in terms of intensity and extension using the finite elements method. Three-dimensional model was generated using computed tomography data of young male patient. Virtual loads were applied on the infra-orbital rim and the eyeball separately. Von Mises stress and equivalent elastic strain were examined in each simulation. The simulation predicted fractures on the infra-orbital rim and orbital floor when simulating the buckling mechanism, and on the orbital floor and mesial wall when simulating the hydraulic mechanism. Biomechanical studies are essential in understanding maxillofacial fractures mechanisms. Our results ascertained and confirmed what is seen clinically and explained the two mechanisms of blow-out fractures.